Biallelic VPS41 Variants in Autosomal Recessive Spinocerebellar Ataxia 29 Resolved by Long‐Read Sequencing and RNA Analysis - Natsuki Nakamura; Yosuke Nishio; Hiromi Nyuzuki; Ai Fukushima; Masaki Miura; Yu Kobayashi; Risako Ishioka; Kotaro Tsukada; Yasuyoshi Oka; Koyo Tsujikawa; Hironobu Morinaga; Mie Inaba; et al. (Molecular Genetics & Genomic Medicine, 2026)
ABSTRACT Background Biallelic variants in VPS41 , encoding a subunit of the HOPS complex, cause autosomal recessive spinocerebellar ataxia 29 (SCAR29), a rare neurodevelopmental disorder with an incompletely defined phenotypic and molecular spectrum. Methods We investigated a 24‐year‐old man with cerebellar ataxia, hypotonia, and intellectual disability. Exome sequencing identified four candidate VPS41 variants. Because maternal DNA was unavailable, long‐read genome sequencing was performed to determine allelic configuration, followed by RNA and protein analyses. Results In addition to typical SCAR29 features, the patient showed previously unreported findings, including swan‐neck deformities and pes cavus. Long‐read genome sequencing demonstrated that two VPS41 variants were in trans. RNA analysis revealed distinct splicing consequences: one allele produced an out‐of‐frame transcript predicted to undergo nonsense‐mediated decay, whereas the other generated an in‐frame exon‐skipped transcript. These complementary defects reduced VPS41 expression at both transcript and protein levels, supporting pathogenicity and variant reclassification. Conclusion Our findings expand the phenotypic spectrum of VPS41 ‐related disease and highlight the value of long‐read allelic resolution in clarifying pathogenic mechanisms in rare genetic disorders.